Restoring fish habitat values on a tropical agricultural floodplain: Learning from two decades of aquatic invasive plant maintenance efforts. (1st December 2020) - Waltham, Nathan J.; Coleman, Laura; Buelow, Christina; Fry, Scott; Burrows, Damien
Abstract: Coastal managers are increasingly challenged with implementing expensive restoration and on-going maintenance programs to reinstate the services and values of floodplains as important fish nursery areas, but access to long-term data to assist with supporting success is lacking. An environmental levy (funded by farmers, Burdekin Shire Council, a local Natural Resource Management group, and Lower Burdekin Water Board) was enacted in 2003 to fund (approximately 20, 000/yr AUD) an ongoing aquatic weed removal program (consisting of an aquatic plant weed harvester that removes floating vegetation to a nearby truck for composting in conjunction with boat weed spraying) designed to maintain the delivery of irrigation water as well as promoting productive fish habitat. We repeated a fish and water quality survey first performed in 2001/2002 (September 2017, May 2018) at 10 lagoons (three clear and seven turbid) on the Burdekin floodplain (north Queensland, Australia) to examine whether these maintenance efforts continue delivering the initial values set nearly 20 years ago. A total of 2267 fish from 24 species were caught, May 2018 (post-wet season) survey yielded more fish (24 species) than the September 2017 (late dry season) survey (19 species) which is close to the results of the 2001/02 survey (post-wet season, 17 species; late dry season, 16 species). A Hydrolab (September 2017) revealed that turbid and clear water lagoons had a similar rhythmic diel temperature cycle that posed no thermal risks to fish. Dissolved oxygen had distinct diel periodicity, with clear lagoons having the widest range, reaching established critical minimum thresholds for some floodplain fish, while turbid lagoons were generally less variable (presumably due to less oxygen demand from biological activity). While as long as sugarcane production occurs, excessive nutrients will necessitate continuance of the aquatic weed program; therefore, the funding model in place must remain. This study advocates the need for long-term maintenance programs facilitated by long-term partnerships, and serves as an exemplar model for managers looking to restore coastal floodplains but are challenged with persistent aquatic weed management issues, not only in Australia but also on floodplains elsewhere. Graphical abstract: Image 1 Highlights: Excessive nutrients from cane farms stimulate excessive aquatic weed growth. An environmental levy has kept excessive aquatic weeds under control. Some lagoons experience critically low dissolved oxygen periods. Fish communities in lagoons increased over the weed management program. Aquatic weed management remains necessary into the future.